2013
DOI: 10.4103/2152-7806.116683
|View full text |Cite
|
Sign up to set email alerts
|

General anesthesia versus combined epidural/general anesthesia for elective lumbar spine disc surgery: A randomized clinical trial comparing the impact of the two methods upon the outcome variables

Abstract: Background:General anesthesia (GA) is the most frequently used technique for lumbar spine disc surgery. The aim of this study was to compare the intraoperative variables and postoperative outcome after GA and combined general/epidural anesthesia (CEG) in patients undergoing elective lumbar spine disk surgery.Methods:Eighty patients who underwent one or two level of laminectomy/discectomy during a 2 year period were enrolled in this randomized controlled trial (RCT). They were randomly selected to undergo GA or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Similarly, Pei et al [ 22 ] demonstrated that epidural anesthesia can provide much better pain relief postoperation, reserve the ability of immune response caused by the stress response leading to an overall better prognosis. Moreover, Khajavi et al [ 23 ] reported that their requirement for analgesics were significantly reduced due to less pain experienced after a lumbar laminectomy procedure. Third, the 5-year survival rate of OC patients who were dosed with GEA was higher than those who received GA. Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pei et al [ 22 ] demonstrated that epidural anesthesia can provide much better pain relief postoperation, reserve the ability of immune response caused by the stress response leading to an overall better prognosis. Moreover, Khajavi et al [ 23 ] reported that their requirement for analgesics were significantly reduced due to less pain experienced after a lumbar laminectomy procedure. Third, the 5-year survival rate of OC patients who were dosed with GEA was higher than those who received GA. Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Khajavi et al . [ 2 ] showed in their study that CGE analgesia could be a better alternative to general anesthesia alone in lumbar disc operations because the combination carries the advantages of both methods.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable acceptance for the use of epidural analgesia, which has minimal side effects, in spine surgery, taking into consideration the proper selection of patients and surgeons;[ 1 ] epidural analgesia provides an acceptable hemodynamic profile, especially when combined with general anesthesia. [ 2 ] However, most previous relevant studies have not addressed the type of drugs used for epidural analgesia in such operations.…”
Section: Introductionmentioning
confidence: 99%
“…For patients undergoing major thoracic and abdominal surgery, neuraxial block can be performed in combination with general anesthesia. Studies showed that, compared with general anesthesia and postoperative intravenous analgesia, combined epidural-general anesthesia and postoperative epidural analgesia decreased the requirement of general anesthetics during surgery and provided better pain relief after surgery [ 36 39 ]. We hypothesize that combined epidural-general anesthesia and epidural analgesia may be superior to general anesthesia and intravenous analgesia in decreasing the incidence of postoperative delirium.…”
Section: Introductionmentioning
confidence: 99%